Preservice teachers’ conceptual metaphors on the lesson planning process - Alarcón-Hernández, Paola; Díaz-Larenas, Claudio; Vásquez-Bustos, Víctor; Venegas-Carrasco, Carolina (Íkala, Revista de Lenguaje y Cultura, 2018)
The aim of this qualitative research is to analyze teacher candidates’ views on lesson planning. The theoretical framework is based on conceptual metaphors as they are understood by Cognitive Linguistics. A written prompt instrument was created to trigger the production of metaphoric expressions. The instrument was run on 125 fifth year teacher candidates from English Language Teaching Programs in three Chilean universities. The data were analyzed through content analysis to elicit metaphors from the data. Six conceptual metaphor categories were defined to mainly describe lesson planning as a help for the teaching and learning process.